Biologija celice: Navodila za laboratorijske vaje - Dariš, Barbara; Lipovšek, Saška (2021)
Cell Biology: Laboratory Work. Laboratory work is divided in 13 chapters. All major topics in the field of cell biology for medicine students are presented.7. 5. 2025 Fourth reprint of the second edition.31. 5. 2023 Third reprint of the second edition.
Keywords: Cell Biology; Microscopy; Laboratory work; university of maribor; faculty of Medicine